2012
DOI: 10.1111/j.1943-278x.2011.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Three Scales Assessing High School Students’ Attitudes and Perceived Norms About Seeking Adult Help for Distress and Suicide Concerns

Abstract: Validated measures that can be administered to school populations are needed to advance knowledge of help-seeking processes and to evaluate suicide prevention programs that target help-seeking. With 6,370 students from 22 high schools, we assessed the psychometric properties of three brief measures: Help-Seeking Acceptability at School, Adult Help for Suicidal Youth, and Reject Codes of Silence. Internal consistency coefficients ranged from 0.64 – 0.84. In support of construct validity, lower scores on each sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 77 publications
0
39
0
Order By: Relevance
“…The scales were also related negatively to maladaptive coping attitudes. These scales identified related but distinct constructs pertaining to help-seeking in two independent samples of high school students using confirmatory factor analysis (Schmeelk-Cone et al 2012). Internal consistency coefficients (Chronbach’s α) presented below are from the present sample.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The scales were also related negatively to maladaptive coping attitudes. These scales identified related but distinct constructs pertaining to help-seeking in two independent samples of high school students using confirmatory factor analysis (Schmeelk-Cone et al 2012). Internal consistency coefficients (Chronbach’s α) presented below are from the present sample.…”
Section: Methodsmentioning
confidence: 99%
“…The Help-Seeking Acceptability at School scale (Schmeelk-Cone et al 2012; Wyman et al 2010) assesses students’ beliefs and perceived norms about getting help for emotional distress. The scale consists of four items (Chronbach’s α = 0.86 for this sample) beginning with the stem, “If I was really upset and needed help…” Students responded to questions covering intentions to seek help (“I would talk to a counselor or other adult at school”), expectations of receiving help (“I believe a counselor or other adult at school could help me”), and perceived norms about seeking help (“My friends…” or “My family……would want me to talk to a counselor or other adult at school”).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work showed that high school students with suicide ideation were more likely to seek adult help if they held positive views toward seeking such help (e.g., belief that friends and family would want them to ask for help), if they perceived adults at school as available and capable of helping suicidal students, and if they believed that the social resources in their lives (family support, positive friends, mentors, healthy activities, generosity, spirituality, mental health, and medical access) would help them get through tough times [12]. Positive help-seeking attitudes are also associated with both a lower risk for suicidal behavior [39] and increased helpseeking behavior among suicidal youth [12]. Numerous studies have demonstrated the importance of youth-adult connections in adolescent health [40][41][42] and for suicidal youth in particular [43][44][45][46][47].…”
Section: Pmentioning
confidence: 99%